Lipidomics: analysis of the lipid composition of cells and subcellular organelles by electrospray Ionization mass spectrometry - Brügger, Britta (Annual review of biochemistry, 2014)
Lipidomics aims to quantitatively define lipid classes, including their molecular species, in biological systems. Lipidomics has experienced rapid progress, mainly because of continuous technical advances in instrumentation that are now enabling quantitative lipid analyses with an unprecedented level of sensitivity and precision. The still-growing category of lipids includes a broad diversity of chemical structures with a wide range of physicochemical properties. Reflecting this diversity, different methods and strategies are being applied to the quantification of lipids. Here, I review state-of-the-art electrospray ionization tandem mass spectrometric approaches and direct infusion to quantitatively assess lipid compositions of cells and subcellular fractions. Finally, I discuss a few examples of the power of mass spectrometry-based lipidomics in addressing cell biological questions.